2014
DOI: 10.1590/0031-1049.2014.54.07
|View full text |Cite
|
Sign up to set email alerts
|

Taxonomy and biogeography of Stephanoxis Simon, 1897 (Aves: Trochilidae)

Abstract: After the description in the 19th century of two hummingbird species currently allocated to the genus Stephanoxis, Peters (1945)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…They seem to be restricted to more humid portions of the forest on mountain slopes or adjacent regions, where the core of their areas of endemism is located, with few exceptions. Main valleys or sedimentary basins seem to be the barriers for those taxa, as described for Paraíba do Sul river and Ribeira do Iguape river [ 64 , 67 , 71 , 73 , 74 , 76 , 79 , 80 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They seem to be restricted to more humid portions of the forest on mountain slopes or adjacent regions, where the core of their areas of endemism is located, with few exceptions. Main valleys or sedimentary basins seem to be the barriers for those taxa, as described for Paraíba do Sul river and Ribeira do Iguape river [ 64 , 67 , 71 , 73 , 74 , 76 , 79 , 80 ].…”
Section: Discussionmentioning
confidence: 99%
“…In general, Serra do Mar, the mountains spreading almost along the whole geographic range herein analyzed, is considered a single area of endemism for forest-dependent vertebrate and plant taxa [22,24,65,66]. However, some studies have shown a more endemic pattern of distribution for species or populations in the southeastern-south coastal mountains and adjacent lowlands of Atlantic Forest, as seen with the area of endemism of harvestmen [25] and spiders [18], specific distributional congruence of vertebrates [67], ecological regionalization of frogs [68], and phylogeographic structure of species of frogs [69][70][71][72], bees [73], vipers [74], birds [75,76], mammals [77,78] and harvestmen [79,80]. The main divergence is found to the south of the state of São Paulo or close to Ribeira do Iguape river valley [6,67,71,73,74,76], but with very different times of divergence between those taxa (~0.39-4.9 m.y.a.)…”
Section: Causal Factors Of Areas Of Endemismmentioning
confidence: 99%
“…This agrees well with the estimate of the origin of the valley ( Almeida and Carneiro 1998 ). Some analyses have shown the same barrier between the southeast and southern blocks but with different estimates of time divergence (∼0.39–4.9 Mya) ( Grazziotin et al 2006 ; Batalha-Filho et al 2010 ; Brunes et al 2010 ; Silva et al 2012 ; Cavarzere et al 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…Second, the Checklist split the Purple-/Violet-crowned Plovercrest (Stephanoxis loddigesii) from Green-crowned Plovercrest (S. lalandii), with a rather high score of 11 (an outlier indeed! ), simultaneously with and in ignorance of Cavarzere et al (2014). On the basis of Cavarzere et al's (2014) evidence, but noting the concordant treatment independently given in the Checklist, Remsen proposed this split to SACC with the comment "In my opinion, by any reasonable standard of comparative degree of phenotypic divergence for allotaxa, these should be treated as separate species."…”
mentioning
confidence: 99%
“…(). On the basis of Cavarzere et al.’s () evidence, but noting the concordant treatment independently given in the Checklist, Remsen proposed this split to SACC with the comment “In my opinion, by any reasonable standard of comparative degree of phenotypic divergence for allotaxa, these should be treated as separate species.” Given his agreement in these cases, how then can he decide that the several hundred original taxonomic changes presented in the Checklist are not worth serious examination?…”
mentioning
confidence: 99%